Injil Lukas dan Preferential Option For The Poor:Perspektif Biblika atas Keadilan Sosial - Juanta, Elkria; Wattimena, Mathius Felix; Korompis, Denny Moody (STT Pelita Dunia, 2025)
This study examines the theological congruence between the modern concept of preferential option for the poor and the narrative of Luke's Gospel. Amidst the pressing challenges of global socio-economic injustice, the Church's social teaching offers an ethical framework that is deeply rooted in biblical tradition. This study argues that the Gospel of Luke not only contains themes of concern for the poor, but also systematically presents a narrative theology that anticipates and provides a solid biblical foundation for this principle of partiality. Using qualitative research methods that integrate exegetical, narrative, and historical-critical analysis, this study analyzes five key passages: the Nazareth Manifesto (Luke 4:18-19), the Magnificat (Luke 1:46-55), the Sermon on the Plain (Luke 6:20-26), The Parable of the Rich Man and Lazarus (Luke 16:19-31), and the story of Zacchaeus' conversion (Luke 19:1-10). The results of the analysis show that Luke consistently describes Jesus' mission and the nature of the Kingdom of God through the lens of social reversal, in which God actively sides with the poor, the oppressed, and the marginalized. The results obtained from this study show that in Luke's theology, siding with the poor is not merely an ethical choice, but a structural principle inherent in God's work of salvation.